Analysis of integration of sustainability in sustainability certifications in the hotel industry - Rodríguez-García, Roberto; Ferrero-Ferrero, Idoya; Fernández-Izquierdo, María Ángeles (Frontiers in Sustainability, 2023)
There is a worldwide consensus that sustainability is the main basis for the recovery of tourism. In this context, tools and standards play an important role to facilitate the integration of the principles of sustainable tourism in practice. Within the tourism sector, the hotel industry is one of the key industries with a high growth rate. The main objective is to carry out an analysis based on the concept of sustainability in the sustainability certifications of the hotel industry, delving into those certifications adopted by the large hotel companies. For this purpose, a comparative analysis of the certification criteria is carried out using as a basis the World Sustainable Tourism Council (GSTC). This article evidences the primacy of the environmental dimension and establishes recommendations that guide holistic and integrated sustainability strategies from a comprehensive perspective that allow the recovery of tourism in general and the sustainable hotel industry in particular.